Breeding behaviour of captive Bewick’s Swans - Evans, Mary E (Wildfowl, 1975)
A history of the first Bewick’s Swans Cygnus columbianus bewickii to breed in captivity, and a survey of captive breeding since, are given. Two breeding pairs were studied. Nest sites and breeding times are described. Both male and female helped shape the nest. During laying the male spent more time on the nest than the female, and during incubation, contrary to what was believed of northern swans, the male was on the nest a third of the time. The nest exodus is described in detail, emphasizing the female’s constant calling, and the male’s preoccupation with the nest. During the first five weeks of life there is strong interaction between female and young, with some growth of independent action, while the male’s role is that of protector. There is a brief account of chick development after five weeks.